Students' Understanding of the Concept in Reaction Rate by Using Diagnostic Test - Habibati*, Habibati; Hanum, Latifah; Nurhayati, Nurhayati; Ahmad, Nur Jahan (Universitas Syiah Kuala, 2025)
One of teachers 21st-century skills is to make qualify evaluation tools. One way to do that is by designing FTMC questions. This study aims to analyze the level of students understanding in SMAN 2 Banda Aceh on reaction rate topic by using FTMC questions. The studys approach used is qualitative and quantitative with descriptive research type. The studys subjects are 35 students of class XI MIPA-4 and 2 chemistry teachers. The data collection technique was obtained by using FTMC test, interview, student and teacher response questionnaires. The studys instruments are FTMC and interview question sheets, student and teacher response questionnaires. The data obtained was analyzed by using excel and percentages formulas. The results showed that the students who were able to understand, not able to understand, misconception, and error of the concepts are 54,5; 2,4; 35,5; and 7,6% respectively. This shows that the students level of understanding is categorized as medium in understanding the concepts. The students' and teachers' responses to FTMC test obtained an average of 46% (poor category) and 85% (good category) respectively. To sum up is that FTMC can be used to analyze students' conceptual understanding in reaction rate material